Madame Bovary. - Flaubert, Gustave, 1821-1880 (Open Road Media, 2014)
One of the world's most celebrated novels, soon to be a major motion picture starring Mia WasikowskaThis indelible portrait of a beautiful woman's aching lust for more--more romance, more glamour, more fun--and her resulting tragic demise, is widely considered one of the finest novels ever written. Flaubert's refusal to condemn his adulterous heroine, a woman trapped as much by circumstance as by her own boundless desires, scandalized nineteenth-century France and resulted in a trial on charges of obscenity. But it is the beauty of the novel's prose, the great care it takes with characters major and minor, and the relentless but elegant thrust of its narrative, that puts Madame Bovary in a class by itself. In the story of a provincial doctor and his wife's tawdry affairs, Gustave Flaubert found the stuff of great literature. A perfect novel about imperfect people, Madame Bovary is the rare classic that exceeds expectations and feels as fresh now as it did the day it was written. This ebook has been professionally proofread to ensure accuracy and readability on all devices.